Personalidad y asertividad en pacientes del centro integral de tratamiento en adicciones Benito Menni, de Quito, periodo mayo- octubre 2016. - Cando Lara, Mayra Alexandra (2017)
The research project is carried out in the "Sacred Heart" Psychiatric Institute of Quito during the period May - October 2016. Evaluating patients with F10 diagnosis. Mental and behavioral disorders due to alcohol consumption, with a sample of 16 patients from the Benito Menni Comprehensive Addiction Treatment Center (CITABM), the sample is chosen using inclusion and exclusion criteria. The research is carried out through the scientific method, the quantitative and non-experimental designs were handled, descriptive, correlational, cross-sectional and field research; And exploratory and comparative levels. Data collection elements are used such as: the MBTI Personality Inventory Form G; And the Rathus Test; In order to know the personality dimensions Extraversion and Introversion and the levels of assertiveness, respectively. The results were analyzed and interpreted using tables and statistical graphs in the program of Microsoft Excel, to consecutively raise the corresponding conclusions and recommendations. At the end of the research the hypothesis is verified, the results indicate that patients with an Introverted personality dimension have a minimum level of Assertiveness, unlike patients with an Extraverted personality dimension who have a maximum level of Assertiveness. For what we propose psychotherapeutic techniques that help improve the level of assertiveness of patients with personality dimension Introvert. Traductor de Google para empresas:Google Translator ToolkitTraductor de sitios webGlobal Market F